Identifying practical approaches to the normalisation of interprofessional collaboration in rural hospitals: A qualitative study among health professionals. Issue 5 (3rd September 2021) - Walmsley, Gemma; Prakash, Viveka; Higham, Sophie; Barraclough, Frances; Pit, Sabrina
ABSTRACT: This qualitative study explores the ideas and experiences of interprofessional collaboration (IPC) among health professionals in rural public hospitals and to propagate its normalization into practice by identifying existing or suggested solutions. The literature focuses largely on the barriers and facilitators to IPC in metropolitan areas and there is room to identify more practical responses for implementing solutions. Semi-structured interviews were conducted with 13 healthcare professionals (October 2018-March 2019). Interviews were audio-recorded, transcribed and underwent thematic analysis to identify themes derived from the dataset. Using the lens of the Normalization Process Theory (NPT) allowed for amalgamation of participant ideas and identification of solutions to implement IPC in practice. Participants' definitions of IPC and Interprofessional Teamwork were incongruous with the current literature, however when provided with formal definitions, participants agreed that they both participated and observed IPC with varying degrees of success. Factors influencing this success included good working relationships and positive workplace cultures, having an understanding of each professions' roles and needs and the hierarchy of professions in conjunction with attitudes of senior healthcare professionals. Solutions to improved IPC and its normalization included induction processes and informal introductions, formalized interprofessional interactions, interprofessional education and positive leadership, such as the 'assertive followership model'. Analyzed in the framework of the normalization process theory, this research shows that IPC is increasingly becoming a coherent, integrated aspect of the healthcare system but there is room for improvement, and cognitive participation in IPC varies across healthcare professionsals. In order to facilitate the normalization process, program and policy makers, hospital administrations and professional associations could consider formalized interprofessional team interactions, formalizing IPC through simple introductions, interprofessional education and positive leadership. Future research could explore through the NPT specific areas of care that benefit from IPC implementation such as community aged-care.